2015
DOI: 10.1108/lhtn-03-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

WeChat in the library: promoting a new virtual reference service using a mobile app

Abstract: Purpose – The purpose of this paper is to address how New York University Shanghai Library utilizes WeChat to support students’ research and information needs. WeChat is a mobile text and voice messaging communication service developed in China. Released in 2011, it currently has over 355 million users worldwide. The paper explores the information exchanges and interactions as well: what are students asking and what they can gain from this app; and features of the app are explored: WeChat can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…Xu et al (2015) stated that approximately one-third of the top 39 academic libraries in China use WeChat as a marketing tool to promote their collections and services to users. Pun (2015) introduced the use of WeChat as a new virtual reference service in New York University Shanghai. To comprehensively determine the current situation of WeChat Libraries applied in the libraries of Chinese colleges, the present study found that there are 39 “Project 985” (Wikipedia, 2015b) university libraries as the basis for the investigation objectives.…”
Section: Wechat Library and Its Applicationsmentioning
confidence: 99%
“…Xu et al (2015) stated that approximately one-third of the top 39 academic libraries in China use WeChat as a marketing tool to promote their collections and services to users. Pun (2015) introduced the use of WeChat as a new virtual reference service in New York University Shanghai. To comprehensively determine the current situation of WeChat Libraries applied in the libraries of Chinese colleges, the present study found that there are 39 “Project 985” (Wikipedia, 2015b) university libraries as the basis for the investigation objectives.…”
Section: Wechat Library and Its Applicationsmentioning
confidence: 99%
“…In addition, for the cognitive needs and self-actualization needs, there were gaps between questionnaire evaluation and behavior data scores in study 2. Pun (2015) mentioned that more and more people used smartphones to obtain information for the satisfaction of their cognitive needs. In the era of fragmented reading, people could easily get a lot of information at their preferred times and places, but few of them would in fact benefit the self-growth of the individual (Liu and Huang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…12 Надаље, анализирајући паметне телефоне и мобилне технологије и њихову улогу у факултетским библиотекама, поједини аутори као почетну тачку наводе смернице у складу са којима су мобилне технологије и паметни телефони изменили начине на које користимо, делимо и стварамо информације, али упркос брзини којом су ове технологије дочекане, академска заједница их је прилично споро прихватала. 13 Управо се могућност распрострањеније употребе мобилних апликација у библиотекарству и библиотекама налази и у предлогу цитираног аутора, који закључује да је неопходно да сами библиотекари препознају и анализирају трендове мобилних апликација, као и да изнађу стратешке одговоре за новонастале изазове.…”
Section: кратак преглед мобилних апликација за библиотекеunclassified